Implementasi Mekanisme Tata Kelola Perusahaan dalam Pelaksanaan Tanggung Jawab Sosial Perusahaan Perbankan Yang Terdaftar di Bursa Efek Indonesia Periode 2016 - 2020 - Hery Haryanto (STIE AMKOP, 2022)
This research spell out implementation mechanisms corporate governance with as variable board size, independent boards, audit committee, managerial ownership, ownership concentration, institutional ownership, foreign ownership, and government ownership of the corporate social responsibility outlined in this study which is backed up by a control variable profitability and firm size. Purposive sampling was the method used for this research. Because samples used for this research meet the criteria, information on the variables employed is required. The study employed a banking firm that was listed on the Indonesia Stock Exchange (BEI) during period 2016 to 2020 as an sample. Ownership concentration and control variable business size have a major impact on social responsibility, according to the findings. The size of the board of directors, the proportion of independent directors, the audit committee, management ownership, institutional ownership, foreign ownership, government ownership, management ownership and control variable profitability had no impact on the company's social responsibility performance. Keywords: Managerial ownership, ownership concentration, institutional ownership, foreign ownership, government ownership, profitability, firm size, corporate social responsibility